Reproductive Subjects and Shifting Global Health Policy Discourses. - Johnson, Candace (Signs: Journal of Women in Culture & Society)
The shift in global health policy from an emphasis on maternal, newborn, and child health (MNCH) to sexual and reproductive health and rights (SRHR) marks a significant victory for many reasons. For feminists, this addresses concerns over the essentialist and pronatalist biases of the maternal frame, and it emancipates women beyond their socioculturally prescribed roles as mothers. Moreover, the shift to a focus on sexual and reproductive health and rights broadens commitments to health services like abortion access, services to address gender-based violence, and support for LGBTQ youth, and to potential beneficiaries beyond pregnant and parturient women. In this article, however, I argue that while this shift in policy focus represents an overdue discursive victory, there are more complex implications for both policies and the individuals that they affect. I suggest a more deliberate approach to the construction of unified, inclusive, reproductive subjects that can be situated in particular contexts and experiences. I also consider the ways in which a unified reproductive subject can combine the maternal with multiple (racialized, LGBTQ, variably abled) subjectivities in order to create possibilities for points of feminist (standpoint) inquiry, grounded normative analysis, and improved understanding of global reproductive justice that are fundamentally antiessentialist and capable of revealing situated knowledges.